Antioxidant activity of Haloxylon scoparium alkaloid extracts from Figuig region (southeastern of Morocco) - Sara Haida; Abdelaziz Kribii; Naima Ait Daoud; Rida Allah Belakhmima; Abderahim Kribii (Universidade de São Paulo, 2022)
Abstract The aim of this paper is to study the chemical composition of alkaloids present in Haloxylon scoparium Pomel extracts and to evaluate their antioxidant capacity. The alkaloids were isolated from two parts of Haloxylon scoparium plant by two extraction protocols. and The quantitative study made it possible to propose the best protocol for the extraction of the alkaloids. Moreover, GC-MS analysis of alkaloid extracts allowed us to determine their chemical composition. Haloxylon scoparium contains four types of alkaloids: tetraisoquinolines, phenylethylamines, tryptolines and tryptamines. The main compounds are the tetraisoquinolines type, the predominant product of which was N-methylsalsoline. These compounds present a great interest for the researchers due to their various pharmacological and biological activities. The antioxidant effect of the different plant extracts was studied by two methods: the ferric reducing antioxidant power (FRAP) and 1,1-diphenyl-2-picryl hydrazyl free radical (DPPH·) scavenging tests. The results show that extracts of root part are more active than those from aerial part; the acetone/water extract is the most powerful. The interesting results obtained in this study will be supplemented by other analyses and biological tests in order to better valorize this plant.